Chlorate ion mediated rutile to anatase reverse phase transformation in the TiO2 nanosystem - Bhosale, Reshma; Hyam, Rajeshkumar S.; Dhanya, P.; Ogale, Satishchandra B. (Dalton Transactions, 2011)
Rutile TiO2 nanoneedles (8 nm x 100 nm) synthesized at room temperature by anodization in perchloric acid (pH < 1) are shown to undergo an interesting reverse phase transformation to anatase nanoparticles (8 nm) at 300 degrees C only if the chlorate ions are maintained in the ambient medium. When chlorate ions are removed by multiple washing, the rutile phase and the needle morphology are maintained. The mechanism of formation of the ion-stabilized solid and its thermal evolution is discussed.

NiS1.97: a new efficient water oxidation catalyst for photoelectrochemical hydrogen generation - Bhosale, Reshma; Kelkar, Sarika A.; Parte, Golu; Fernandes, Rohan; Kothari, Dushyant; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2015)
NiS1.97, a sulfur-deficient dichalcogenide, in nanoscale form, is shown to be a unique and efficient photoelectrochemical (PEC) catalyst for H-2 generation by water splitting. Phase pure NiS1.97 nanomaterial is obtained by converting nickel oxide into sulfide by controlled sulfurization method, which is otherwise difficult to establish. The defect states (sulfur vacancies) in this material increase the carrier density and in turn lead to favorable band line-up with respect to redox potential of water, rendering it to be an effective photoelectrochemical catalyst. The material exhibits a remarkable PEC performance of 1.25 mA/cm(2) vs NHE at 0.68 V in neutral pH, which is almost 1000 times superior as compared with that of the stoichiometric phase of NiS2. The latter is well-known to be a cocatalyst but not as a primary PEC catalyst.
Keywords: dichlacogenide; Faradaic efficiency; Hydrogen generation; NiS1.97; nonstoichiometric; photoelectrochemical catalyst; sulfurization

p-type NiO hybrid visible photodetector - Mallows, John; Planells, Miguel; Thakare, Vishal; Bhosale, Reshma; Ogale, Satishchandra; Robertson, Neil (ACS Applied Materials & Interfaces, 2015)
A novel hybrid visible-light photodetector was created using a planar p-type inorganic NiO layer in a junction with an organic electron acceptor layer. The effect of different oxygen pressures on formation of the NiO layer by pulsed laser deposition shows that higher pressure increases the charge carrier density of the film and lowers the dark current in the device. The addition of a monolayer of small molecules containing conjugated pi systems and carboxyl groups at the device interface was also investigated and with correct alignment of the energy levels improves the device performance with respect to the quantum efficiency, responsivity, and photogeneration. The thickness of the Organic layer was also optimized for the device, giving a responsivity of 1.54 X 10(-2) A W-1 in 460 nm light.
Keywords: nickel oxide; organic; oxygen vacancies; photodetector; pulsed laser deposition; surface modifier

Direct Z-scheme g-C3N4/FeWO4 nanocomposite for enhanced and selective photocatalytic CO2 reduction under visible light - Bhosale, Reshma; Jain, Srashti; Vinod, Chathakudath Prabhakaran; Kumar, Santosh; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2019)
Photocatalytic reduction of CO2 to renewable solar fuels is considered to be a promising strategy to simultaneously solve both global warming and energy crises. However, development of a superior photocatalytic system with high product selectivity for CO2 reduction under solar light is the prime requisite. Herein, a series of nature-inspired Z-scheme g C3N4/FeWO4 composites are prepared for higher performance and selective CO2 reduction to CO as solar fuel under solar light. The novel direct Z-scheme coupling of the visible light-active FeWO4 nanoparticles with C3N4 nanosheets is seen to exhibit excellent performance for CO production with a rate of 6 mu mol/g/h at an ambient temperature, almost 6 times higher compared to pristine C3N4 and 15 times higher than pristine FeWO4. More importantly, selectivity for CO is 100% over other carbon products from CO, reduction and more than 90% over. H-2 products from water splitting. Our results clearly demonstrate that the staggered band structure between FeWO4 and C3N4 reflecting the nature-inspired Z-scheme system not only favors superior spatial separation of the electron hole pair in g-C3N4/FeWO4 but also shows good reusability. The present work provides unprecedented insights for constructing the direct Z-scheme by mimicking the nature for high performance and selective photocatalytic CO2 reduction into solar fuels under solar light.
Keywords: C3N4; CO2 reduction; FeWO4; Photocatalysis; solar fuels; Z-scheme

Photocatalytic CO2 reduction to syngas using nickel phosphide-loaded CdS under visible light irradiation - Yadav, Poonam; Kumar, Santosh; Velankanni, Nandhakumar; Kuehne, Thomas D.; Gosavi, Suresh; Raghupathy, Ramya Kormath Madam; Bhosale, Reshma; Held, Georg; Shelke, Manjusha; Ogale, Satishchandra (Journal of Physics-Energy, 2024)
Photocatalytic CO2 reduction is a sustainable pathway to produce syngas (H-2 + CO), which is a key feedstock for the production of several important liquid fuels on the industrial scale. However, achieving an appropriate tunable ratio of H-2:CO in syngas for commercial purposes is a challenging task. In this work, we present a low-cost and non-noble metal, phosphide-based co-catalyst-Ni2P-loaded cadmium sulfide (CdS) photocatalyst system, for photocatalytic CO2 reduction. As a co-catalyst, Ni2P fosters an efficient charge separation of photoexcited charges generated in the CdS production of syngas. In total, 3 wt.% Ni2P/CdS exhibited exceptional performance of 50.6 mu mol g(-1) h(-1) in the CO evolution rate and 115 mu mol g(-1) h(-1) in the H-2 evolution rate, with a syngas composition varying from 2 to 4 in the H-2:CO ratio. Furthermore, first-principles density functional theory calculations were performed to study the surface energetics of the catalyst system and the results are found to be consistent with our experimental findings. Indeed, they establish that the composite favors CO2 photoreduction into syngas more efficiently than pure surfaces.
Keywords: CdS; CO2 reduction; Photocatalysis; Syngas; transition metal phosphides